Interdisciplinary management of delayed replantation of avulsed immature maxillary incisivus centralis teeth: A case study - Inayah, Yayah; Nurwahidah, Nurwahidah; Agustin, Rosdiana (Journal of Case Reports in Dental Medicine, 2024)
Objective: The aim of this treatment is to preserve the tooth and surrounding bone for several years.Methods: A nine-year-old girl presented with avulsion of both maxillary central incisor teeth due to falling off a bicycle after 1 day of previous incident. Treatment guidelines for immature avulse permanent teeth with prolonged extra-oral time were performed for the teeth and extra-oral endodontic treatment was completed by the pediatric dentist. After being repositioned and fixed by the oral surgeon using an arch bar, the tooth was stabilized for 8 weeks, 20 weeks and prophylactic antibiotics were prescribed. Clinical and radiographic controls were done after 2 months, 4 months and 6 months. During this period there was still no improvement in the attachment of the avulsed tooth to the surrounding bone, and it is currently under treatment control with a composite wire splint.Results: The prevalence of avulsion cases in children increases between the ages of 7 to 9 years due to incomplete root development and minimal resistance of the alveolar bone/periodontal ligament (PDL) to extrusion forces during the period of tooth eruption.Conclusion: Dental avulsion replantation treatment should be performed immediately but delayed replantation cases can still be performed.